IMMUNE STATE IN PATIENTS WITH HEMATOLOGICAL MALIGNANCIES AT LATE TERMS AFTER AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION - N. V. Minaeva; T. P. Zagoskina; E. P. Svedentsov; G. A. Zaitceva; N. V. Isaeva; N. А. Zorina (Медицинская иммунология)
Abstract. Autologous hematopoietic stem cell transplantation (auto-HSCT) is one of the most effective methods for treatment of patients with various forms of hemoblastoses, both in adults and children. However, high-dose chemotherapy protocols used in this procedure are characterized by pronounced myeloand immunotoxicity. Appropriate data concerning immune state at long terms after high-dose chemotherapy and auto-HSCT are sparse and controversial, and there is no consensus on time dynamics of immune system reconstitution. The aim of this study was a comprehensive evaluation of immunity in recipients of auto-HSCT at longer terms. Clinical and immunological testing was performed in ninety-eight patients with hematological malignancies before starting a high-dose chemotherapy, and at late post-transplant period. The state of cellular immunity was assessed as expression of surface CD3+, CD4+, CD8+, CD16+, CD19+ lymphocyte antigens. Humoral immunity was evaluated by serum IgG, IgA, and IgM levels. The studies have revealed disorders of cellular and humoral immunity, as well as nonspecific immune resistance factors in recipients of autologous hematopoietic stem cells at late terms post-transplant. Immune reconstitution in patients receiving highdose consolidation treatment followed by auto-HSCT takes longer time than in patients who did not receive autologous hematopoietic stem cells. Severity of these disturbances and immune reconstitution rates depend on the type of conditioning regimen, and the source of haematopoietic stem cells used for transplantation.